Pengaruh Kualitas Produk Dan Citra Perusahaan Terhadap Kepuasan Pelanggan CV. UI3 Media Palembang - Dwijayanti, Suci; Pramuditha, Charisma Ayu (MDP Student Conference, 2024)
This study ains to analyze the effect of product quality and corporate image on customer satisfaction at CV. UI3 Media Palembang. The population of this research is the consumers of CV. UI3 Media Palembang. The sample used in this study was 168 using the slovin formula. In this study, using multiple linear regression analysis techniques to test hypotheses and data management using SPSS 21. The result showed that product quality, and corporate image have a partial effect on customer satisfaction at CV. UI3 Media Palembang. Simultaneously shows that there is an influence of product quality and corporate image have an affect on customer satisfaction at CV. UI3 Media Palembang.